Chronic Treatment with a Phytosomal Preparation Containing Centella asiatica L. and Curcuma longa L. Affects Local Protein Synthesis by Modulating the BDNF-mTOR-S6 Pathway - Sbrini, Giulia (Biomedicines, 2020)
Brain derived neurotrophic factor (Bdnf) is the most diffuse neurotrophin in the central nervous system and it is crucial for the proper brain development and maintenance. Indeed, through the binding to its high affinity receptor TRKB and the activation of different intracellular cascades, it boosts cell survival, neurite growth and spine maturations mechanisms. Here, we evaluated if the chronic oral treatment for 10 days with a phytosomal preparation containing Centella asiatica L. and Curcuma longa L. could improve Bdnf levels in the prefrontal cortex of adult rats. Interestingly we found an increased expression of Bdnf with main effect of the treatment on the mTOR-S6 downstream signaling pathway. Accordingly, we found an increase in the expression of eukaryotic elongation factor (eEF2) with a shift towards the phosphorylated form thus increasing the transcription of Oligophrenin-1, a protein carrying the upstream Open Reading Frame (uORF) which reduction is paralleled by memory dysfunctions. These results show the ability of the phytosome to enhance mTOR-S6 regulated transcription and suggest the possibility to use this preparation in subjects with impairments in neuroplastic mechanisms, memory and cognitive abilities.